Knowledge, Attitude and Perception on Halal Dietary Supplements among Sport Students in Universities of Malaysia - Khairiah Binti Santa; Eddy Yusuf; Neni Widiasmoro Binti Selamat (Journal of Food and Pharmaceutical Sciences, 2019)
This is a cross-sectional study. It was disbursed between April 2019 and May 2019, using module andself-administered questionnaires to evaluate the Knowledge, Attitude and Perception (KAP) regarding halalsupplement among sport students in public universities of Malaysia (UITM, UM and UPSI). Aim for this studyis to find out the awareness level of halal dietary supplement among sport students’ in three public universities.The study was conducted on a sample of n=167. Inclusion criteria was a full time students of sport school ofpublic university in Malaysia. Data was collected through module presentation and pre-post questionnaires.Results discovered that student have a good knowledge and positive attitude and perception regarding halalsupplement after intervention. Mean knowledge score out of maximum possible 8 was 0.96±0.101, mean attitudescore out of maximum possible score of 50 was 4.50±0.623, while mean perception score out of maximumpossible score of 75 was 4.69±0.551. Mean overall KAP score out of maximum possible score of 167 was3.38±0.365. There was a significant, positive and fair correlation between knowledge and attitude, knowledgeand perception and attitude and perception which is all p=0.000. Result shows that the better knowledge thestudents have on halal supplement, the better their perception and attitude is towards halal supplement. P valueof 0.05 or less was taken as statistically significant.